Using GIS in an Earth Sciences field course for quantitative exploration, data management and digital mapping. Issue 2 (3rd April 2017) - Marra, Wouter A.; van de Grint, Liesbeth; Alberti, Koko; Karssenberg, Derek
Abstract: Field courses are essential for subjects like Earth Sciences, Geography and Ecology. In these topics, GIS is used to manage and analyse spatial data, and offers quantitative methods that are beneficial for fieldwork. This paper presents changes made to a first-year Earth Sciences field course in the French Alps, where new GIS methods were introduced. Students use GIS in preparation to explore their research area using an elevation model and satellite images, formulate hypotheses and plan the fieldwork. During the fieldwork, a pilot group managed their field-observations using GIS and made digital maps. Students praise the use of quantitative digital maps in the preparation. Students made use of the available techniques during the fieldwork, although this could be further intensified. Some students were extra motivated due to the technical nature as well as the additional analytical possibilities. The use of GIS was experienced as a steep learning curve by students, and not all staff members are confident in supervising students using GIS, which calls for a sufficient preparation and training of both students and staff. The use of GIS adds abstract analyses and quantitative assessment, which is a complementary learning style to fieldwork that mostly focuses on practical skills.